Determining International Postgraduate Students’ Travel Behavior In Malaysia - Heidari, Hanieh Varasteh (2013)
This study examines international students travel behaviors in an attempt to find out important factors influencing their travel preferences and activities. It also aims to provide useful information about significance of international students’ travel behavior to the tourism industry followed by a discussion of the limitations in the literature and try to overcome the identified gaps. The study further attempts to provide detailed information on travel preferences, travel related activities, destinations visited, sources using for obtaining information about preferred destinations and to investigate the overall expenditure by international students while on holiday in Malaysia. Consequently it contributes to the existing literature and also lays a foundation for further research to be conducted. Finding of this quantitative study are based on the responses obtained from a self-administered survey of 409 International postgraduate students of research universities (UPM, USM, UM, UTM, and UKM) in Malaysia. Through the findings a new travel behavior model was generated which has been supported by the empirical data and added new variables and constructs to the existing models of travel behaviors. The empirical data further, found the relationship among socio-demographic characteristics of international student travelers, information sources, travel preferences, and activities undertaken while travelling. The moderating effect of information source on relationship between nationality and travel behavior also has been identified by the current study for the first time.